THE EXPRESSION OF UNIVERSAL HUMAN AND NATIONAL CHARACTERISTICS IN NARRATIVES ABOUT YUSUF (Scientific journal of the Fergana State University, 2026)
Examples of verbal art with migrating (wandering) plots, widely spread among various peoples, as well as works that emerged under the influence of literary contacts, are not only unique historical sources of their time but also vivid expressions of the literary and aesthetic potential and spiritual and moral values of particular peoples. The plot of the story of Yusuf (Joseph the Beautiful) is one of such phenomena in world literature. The article examines the historical-philosophical and literary-aesthetic development of this plot, which served as a distinctive mirror of the literary, cultural, and social life of different eras and underwent stages of evolution from myth to metaphor, from symbol to allegory.